Oxford dictionary of english - Pearsall, Judy (Oxford Universty Press, OXFORD, 2003)
"The Oxford English Dictionary (OED), like its abridged version, the Shorter Oxford English Dictionary, is written on historical principles and traces the development of each word's meaning and form from its first appearance in English. Oxford's other English dictionaries, following the style of the ground-breaking New Oxford Dictionary of English (1998), present words according to their use and frequency in modern English."--Jacket